Probiotics and Oral Complications of Antineoplastic Therapy in Head and Neck Cancer: A Systematic Review and Meta-Analysis - Tanya Pereira-Riveros; Enric Jané-Salas; José López-López; Constanza Saka-Herran; Isabel Linares-Galiana; Teresa Vinuesa-Aumedes (Dentistry Journal, 2025)
Background/Objectives: Patients with head and neck cancer frequently develop oral complications such as oral mucositis, infections, necrosis, and periodontal disease among others as a consequence of antineoplastic therapy. It is mainly radiotherapy that promotes oral dysbiosis, favouring the overgrowth of opportunistic microorganisms. Identifying effective adjunctive strategies to prevent or mitigate these adverse effects is crucial. Recent studies have suggested that probiotics could be used to restore microbial homeostasis and modulate inflammatory responses in the oral cavity. This systematic review and meta-analysis assessed the efficacy of probiotics in alleviating oral complications associated with antineoplastic treatments in this patient population. Methods: A comprehensive search was conducted in PubMed, LILACS, Scopus and the Cochrane Central Register of Controlled Trials, following the PRISMA 2020 guidelines. Only randomised controlled trials (RCTs) were included. Results: Nine eligible RCTs were analysed using a random-effects meta-analysis. Probiotic use was significantly associated with a reduced incidence of severe (grade 3–4) oral mucositis (RR = 0.58; 95% CI: 0.41–0.81). Moderate benefits were also observed in modulating the oral microbiota and reducing levels of pathogenic bacteria and Candida spp. However, no significant improvements were noted in periodontal parameters or plaque indices. Conclusions: Probiotics show promise in the management of oral mucositis, but further well-designed trials are needed to evaluate their broader impact on oral health during cancer therapy. This review is not registered on PROSPERO.